O BULLYING NO AMBIENTE ESCOLAR: pesquisa realizada na Escola Municipal de Ensino Fundamental José Maria Rodrigues Viegas Junior, em Melgaço/PA - SOUZA, Yan Luis Lima de (2024)
This paper aims to address bullying in the school environment, and present the results of research conducted at the José Maria Rodrigues Viegas Junior Elementary School in Melgaço / PA, aiming to diagnose the incidence or not of bullying cases in school. . The initial motivation to approach the theme was due to the lack of academic productions about bullying in the Marajoara region, and the concern about reports about violence among students within the school environment in Melgaço / PA. To theoretically substantiate this work, Ariès (1981); Rizinni and Pilotti (2011) were used to guide the child's story, to characterize bullying from a multifocal view and striving for national authors, Silva (2015); Gomes and Sanzovo (2013); Lopes Neto (2005); Maldonado (2011); Fante (2015), still some international researchers, such as Olweus (1997); Rigby (2019) and Koo (2007). The research applied to that school had descriptive purposes, and two data collection instruments were used: the questionnaire, with the faculty and the technical-administrative staff; and the semi- structured interview with the students. The results of the research indicate the existence of cases of bullying among students in the years 2018 and 2019, especially in verbal form and in derogatory graffiti in the bathrooms. In addition, there was the absence of projects and actions aimed at combating and preventing bullying in the school, which can be very harmful to those who are victimized by bullying.